2012
DOI: 10.1093/jnci/djs455
|View full text |Cite
|
Sign up to set email alerts
|

International Multicenter Tool to Predict the Risk of Nonsentinel Node Metastases in Breast Cancer

Abstract: We present a novel, international, multicenter, predictive tool to assess the risk of additional axillary metastases after tumor-positive sentinel node biopsy in breast cancer. The predictive model performed well in internal and external validation but needs to be further studied in each center before application to clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
55
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 29 publications
10
55
0
4
Order By: Relevance
“…The last proposed international model from multiple centers in Europe, however, has not been validated to date. To the best of our knowledge, the present study is the first to validate the Rome and European models (Lombardi et al, 2011;Meretoja et al, 2012). Applying the MD Anderson model to our dataset demonstrated that it was the most suitable model for our patients, generating an AUC of 0.86, which is the second highest AUC after the present model.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The last proposed international model from multiple centers in Europe, however, has not been validated to date. To the best of our knowledge, the present study is the first to validate the Rome and European models (Lombardi et al, 2011;Meretoja et al, 2012). Applying the MD Anderson model to our dataset demonstrated that it was the most suitable model for our patients, generating an AUC of 0.86, which is the second highest AUC after the present model.…”
Section: Discussionmentioning
confidence: 58%
“…The main problem is determining which patients with positive SLNs should undergo completion ALND and which should not. To find a solution to this problem, predictive factors for non-SLN metastasis among patients with positive SLN have been investigated, and many nomograms or scoring systems have been developed to predict the likelihood of non-SLN metastasis using predictive factors (Van Zee et al, 2003;Degnim et al, 2005;Chapgar et al, 2006;Pal et al, 2008;Kohrt et al, 2008;Cho et al, 2008;Coufal et al, 2009;Gur et al, 2010;Perhavec et al, 2010;Lombardi, et al, 2011;Mittendorf et al, 2012;Meretoja et al, 2012;Derici et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of sentinel lymph nodes dissected and the ratio of metastatic/dissected sentinel nodes, tumor burden in metastatic sentinel node and extracapsular invasion to the surrounding tissue were investigated using both univariant and multivariant analyses and found related with non-sentinel lymph node involvement in various studies (17)(18)(19)(20)(21)(22). Considering our findings, it can be stated that when more than half of the dissected sentinel nodes are infiltrated, the likelihood of having metastasis in the rest of the axillary lymph nodes significantly increases.…”
Section: Discussionmentioning
confidence: 99%
“…Plusieurs modèles prédictifs du risque d'atteinte de ganglion non sentinelle ont été développés mais uniquement quelques modèles ont été dédiés aux patientes chez qui il a été détecté des cellules isolées ou des micrométastases des ganglions sentinelles [10,11,[14][15][16]. Les critères prédictifs significatifs ont été principalement les suivants : la taille pathologique de la tumeur infiltrante, la présence d'emboles vasculaires, le mode de détection des micromé-tastases ou leur taille, le type histologique de la tumeur, le nombre de ganglions sentinelles envahis ou le ratio par rapport au nombre de ganglions sentinelles prélevés, le caractère multicentrique de la tumeur.…”
Section: Modèles Prédictifs Du Taux De Ganglions Non Sentinelles Envahisunclassified